Benefits associated with the implementation of biological control programmes in Latin America - Colmenarez, Yelitza C. [UNESP]; Vasquez, Carlos (Springer Nature, 2024)
Agriculture in Latin America plays a significant role in the region’s economy, food security, and rural development. Although pest control has traditionally relied on chemicals, there is increasing adoption of sustainable agricultural practices. Thus, in recent years, there has been a growing emphasis on sustainable agriculture practices, including biological control, to minimise environmental impact, conserve natural resources, and ensure long-term agricultural productivity. In Latin America, high biodiversity enhances biological control, both classical and augmentative biological control. The use of biological control agents allows farmers to produce their crops whilst reducing the use of chemicals in agriculture. In addition, biological control opens new market opportunities for farmers and job options for youth in rural areas. Maximal benefits will however be attained only after adoption of biological control practices and when an effective interaction among key stakeholders is achieved. Thus, farmers and consumers can reap the benefits of biological control, which can incentivise and accelerate adoption at the field level. To evaluate the socio-economic benefits of biological control, establishing multidisciplinary teams to conduct the studies is crucial. The current article explores the benefits resulting from the implementation of biological control programmes, highlighting social benefits. In addition, as part of the Plantwise programme, created to assist agricultural production with a sustainable perspective, data on the use of biopesticides in some countries are discussed in the context of sustainable production looking forward to reinforcing food security and safety in Latin America.
Keywords: Benefits; Biological control; Food security; Integrated pest management; Latin America; Sustainable production